Consider the sum $$\sum_{i=1}^n (2i-1)^2 = 1^2+3^2+...+(2n-1)^2.$$

I want to find a closed formula for this sum, however I'm not sure how to do this. I don't mind if you don't give me the answer but it would be much appreciated. I would rather have a link or anything that helps me understand to get to the answer.

EDIT: I Found this question in a calculus book so I don't really know which tag it should be.

  • 5
    $\begingroup$ The statement itself is wrong to begin with. $\displaystyle \sum_{i=1}^n (2i-1)^2 = 1^2+3^2+5^2+\cdots+(2n-1)^2$. $\endgroup$
    – DHMO
    Apr 12 '17 at 14:15
  • $\begingroup$ hmm..what do you mean? $\endgroup$
    – Tom Harry
    Apr 12 '17 at 14:18
  • 1
    $\begingroup$ (2n-1) is odd integer if n is integer. $\endgroup$
    – jonsno
    Apr 12 '17 at 14:19
  • $\begingroup$ Also, it should end on $(2n-1)^2$ and not $(2i-1)^2$ which makes no sense. $\endgroup$ Apr 12 '17 at 14:20
  • $\begingroup$ What @DHMO is saying is that $i$ is defined only within the sum. Therefore, it can't appear on the RHS. Instead, the RHS should have only the variable $n$. $\endgroup$ Apr 12 '17 at 14:20

Hint: $\sum_{i=1}^ni^2=\frac{n(n+1)(2n+1)}{6}$ and $\sum_{i=1}^ni=\frac{n(n+1)}{2}$. And last but not least $$(2i-1)^2=4i^2-4i+1.$$

Edit: Let's prove that $\sum_{i=1}^ni=\frac{n(n+1)}{2}$. We proceed by induction on $n$. If $n=1$ the statement is trivial. Now suppose the statement holds for $n\geq 1$. Then \begin{eqnarray}\sum_{i=1}^{n+1}i&=&\sum_{i=1}^ni+(n+1)\\ &=&\frac{n(n+1)}{2}+(n+1)\\ &=& (n+1)(\frac{n}{2}+1)\\ &=& \frac{(n+1)(n+2)}{2}.\end{eqnarray} Here we used the induction hypothesis in the second equation. This proves the statement by induction. You can prove the other formula in a similar fashion.

  • $\begingroup$ $\frac{4n(n+1)(2n+1)}{6} - \frac{4n(n+1)}{2} + n$ will it look something like this? and where can i learn about these formulas etc. $\endgroup$
    – Tom Harry
    Apr 12 '17 at 14:29
  • $\begingroup$ Yes, if you work it out you should get $\frac{1}{3}n(4n^2-1).$ I'll edit my answer and show you how to prove one the formulas. $\endgroup$ Apr 12 '17 at 14:34


We have

$$1^2+3^2+5^2+... (2n-1)^2=$$

$=\sum $ odd$^2$=$\sum$ all$^2 $-$\sum $even$^2=$

$$\sum_{k=1}^{2n} k^2-(2^2+4^2+...4n^2)= $$

$$\sum_{k=1}^{2n}k^2-4\sum_{k=1}^n k^2=$$

$$\boxed {\color {green}{\frac {n(4n^2-1)}{3}}}$$

for $n=2$, we have $10 $ , for $n=3$, we find $35$ and for $n=4$, it is $84$.

  • $\begingroup$ i don't understand how you got to $\sum_1^{2n} k^2-(2^2+4^2+...4n^2)=$ $\endgroup$
    – Tom Harry
    Apr 12 '17 at 14:38
  • $\begingroup$ plus what does $\sum_1^{2n} $ this even mean. How can it be 2n isnt it essentially just n $\endgroup$
    – Tom Harry
    Apr 12 '17 at 14:40
  • $\begingroup$ @TomHarry I edited it . now it is clear. $\endgroup$ Apr 12 '17 at 14:43
  • $\begingroup$ doesn't sigma all^2 = $\sum_{k=1}^{n} k^2$ and if so why do u have $\sum_{k=1}^{2n} k^2$ $\endgroup$
    – Tom Harry
    Apr 13 '17 at 16:05

Hint: Write $f(n) = \sum_{i=1}^n (2i-1)^2$. You can start by hypothesizing that the sum of squares is a cubic $f(n) = an^3 + bn^2 + cn + d$ (as a sort of discrete analogy with the integration formula $\int x^2\, dx = x^3/3 + C$). Then $(2n+1)^2 = f(n+1) - f(n) = a (3n^2 + 3n + 1) + b(2n + 1) + c$, which gets you the constants $a, b, c$, and you can find $d$ from $f(1) = 1$. Verifying this formula is an easy proof by induction.


$$\begin{align} \sum_{i=1}^n (2i-1)^2 &=\sum_{i=1}^n \binom {2i-1}2+\binom {2i}2&&\text(*)\\ &=\sum_{r=0}^{2n}\binom r2\color{lightgrey}{=\sum_{r=2}^{2n}\binom r2}\\ &=\color{red}{\binom {2n+1}3}&& \text(**)\\ &\color{lightgrey}{=\frac {(2n+1)(2n)(2n-1)}6}\\ &\color{lightgrey}{=\frac 13 n(2n-1)(2n+1)}\\ &\color{lightgrey}{=\frac 13 n(4n^2-1)} \end{align}$$

*Note that $\;\;\;R^2=\binom R2+\binom {R+1}2$.
**Using the Hockey-stick identity


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.